Arch branch endografts for arch aneurysms associated with bovine anomaly. (February 2019) - Law, Y; Chan, YC; Cheng, SW
Bovine aortic arch is known to be associated with an increased rate of aortic arch expansion. The most frequently observed human variant of bovine aortic arch is a common origin of the innominate trunk and left common carotid artery. This is a report of two patients who had successful custom-made arch branch endograft treatment for an arch aneurysm associated with bovine arch anomaly. Modular endovascular repair of aortic arch aneurysms using an inner-branched device adds to the armamentarium of treatment options, and is a minimally invasive management modality without the need for sternotomy or intraoperative extracorporeal bypass.